Philippoi or Philippopolis, Nicopolis Epirus or Nicopolis ad Nestum - DIMITROV, Ivan (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
In the Biblical science, including New Testament research, assumptions and hypotheses are often expressed, and great efforts are made to defend opinions that differ from traditionally accepted facts about biblical personalities or events. Such an example are the aspirations of some ambitious Bulgarian scholars to redraw the path of the preaching activity of the apostle Paul on the Balkan Peninsula arguing that he went not to the city of Philippoi, but to the city of Philippopolis. The other ancient city that is claimed to be a biblical site is the town of Nicopolis ad Nestum in the middle reaches of the Mesta River in southern Bulgaria. Strange as it may seem, some researchers claim that this is the city where apostle Paul wished to spend the winter months, as he wrote to his disciple Titus (Tit 3:12), and not Nicopolis Epirus. The reasons for the interest in such hypotheses are clear: everyone is seduced by the thought that his place or his country had a glorious but already forgotten history; that only more famous countries and cities are considered to be the centers of events in world history, including Christian history. But history is a memory of truth, not of imaginary events.